Farmers’ participation in the Kisan Call Centre – A critical evaluation - P. Lavanya; C. Karthikeyan; J. Venkatapirabu (Journal of Agricultural Extension Management, 2025)
At present, the Kisan Call Centres are operating in 13 states all over India. The call centre functions with a toll free number ’ 1551 ’ throughout the country and the call lands on to the nearby centre in the state where the call is made. Queries related to agriculture and allied sectors are being addressed through these centres